2009
DOI: 10.1053/j.gastro.2008.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Folate Deficiency Induces Genomic Uracil Misincorporation and Hypomethylation But Does Not Increase DNA Point Mutations

Abstract: Background and Aims-Epidemiologic studies have linked nutritional folate deficiency to an increased risk of cancer, but recent trials suggest that folate supplementation does not protect against tumor formation. Our aim was to analyze the genetic and epigenetic consequences of folate deficiency and to investigate whether impairment of the uracil base excision repair pathway can enhance its effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 43 publications
1
72
1
Order By: Relevance
“…Folate is an essential cofactor for one-carbon methyl transfer reactions and crucial for a variety of biological processes, such as synthesis and repair of DNA (Blount et al 1997;Kronenberg et al 2008;Linhart et al 2008), regulation of gene expression (Ghoshal et al 2006;Pogribny et al 2008), and synthesis of amino acids and neurotransmitters (Fournier et al 2002;Shinohara et al 2006). Since the 1940s, folate-deficient states and inborn errors of folate metabolism including defective transport have increasingly been recognized to play a role in the development of a macrocytic anemia, atherosclerosis, thrombosis, neuropsychiatric disorders, and neural tube defects (Surtees et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Folate is an essential cofactor for one-carbon methyl transfer reactions and crucial for a variety of biological processes, such as synthesis and repair of DNA (Blount et al 1997;Kronenberg et al 2008;Linhart et al 2008), regulation of gene expression (Ghoshal et al 2006;Pogribny et al 2008), and synthesis of amino acids and neurotransmitters (Fournier et al 2002;Shinohara et al 2006). Since the 1940s, folate-deficient states and inborn errors of folate metabolism including defective transport have increasingly been recognized to play a role in the development of a macrocytic anemia, atherosclerosis, thrombosis, neuropsychiatric disorders, and neural tube defects (Surtees et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the data on the effects of folate and Ung deficiency on point mutations showed that folate deficiency had no significant effect on the frequency or spectrum of point mutations on wild-type or Ung -/-mice. In particular, the study failed to detect an increase in point mutations at T:A base pairs, resulting from repair of uracil misincorporation (Linhart et al, 2009). The authors concluded that although folate deficiency causes an increase in genomic uracil content through uracil misincorporation, it does not lead to an increase in DNA point mutations; nor does it increase transition mutations at CpG sites.…”
Section: Effects Of Diet On Genome Stabilitymentioning
confidence: 94%
“…The resultant U:A base pairs are potentially mutagenic because of secondary repair activity that can generate abasic sites (Auerbach et al, 2005), creating point mutations or chromosomal breaks at T:A base pairs (Linhart et al, 2009). Subsequently, folate deficiency is believed to dramatically decrease DNA repair efficiency as it disturbs nucleotide syntheses, promoting DNA damage, via chromosomal breakage (Sibany et al, 2002;Zhang et al, 2003).…”
Section: Effects Of Diet On Genome Stabilitymentioning
confidence: 99%
See 2 more Smart Citations